1996
DOI: 10.1007/bf02246661
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, double blind, controlled placebo-phase in trial of low dose phenelzine in the chronic fatigue syndrome

Abstract: Because of the striking similarity of the clinical manifestations produced by use of the drug reserpine and seen in patients with the chronic fatigue syndrome (CFS), we theorized that CFS was a disorder of reduced central sympathetic drive. Because of the pharmacology of control of this central sympathetic system, we further postulated that CFS symptoms would respond quickly to low dose treatment with a monamine oxidase inhibitor. To test these hypotheses, we designed a randomized, double blind placebo control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(25 citation statements)
references
References 18 publications
0
23
0
1
Order By: Relevance
“…A mix of validated tools for different dimensions or domains is needed to take into consideration the wide and pervasive impact of this ill-* References 22,26,[29][30][31]33,35,37,43,45,51. ness on many domains. A comprehensive review of outcome measures currently used would be the first step in this process.…”
Section: Commentmentioning
confidence: 99%
“…A mix of validated tools for different dimensions or domains is needed to take into consideration the wide and pervasive impact of this ill-* References 22,26,[29][30][31]33,35,37,43,45,51. ness on many domains. A comprehensive review of outcome measures currently used would be the first step in this process.…”
Section: Commentmentioning
confidence: 99%
“…Evidence for the latter possibilities does exist in the literature on CFS clinical trials [18]. However, our own previous trial [5] plus another on fluoxetine [19] found no evidence for either spontaneous improvement or for a placebo effect. One explanation suggested for these results is that the study patients had a severe form of CSF which might be less responsive to treatment [20].…”
Section: Discussionmentioning
confidence: 81%
“…Of these, the pharmaceutical option is the weakest, and so current drug treatment is directed toward symptomatic relief. In a recent double-blind, placebo-controlled trial of low-dose phenelzine in a small number of patients, we reported a very small but statistically significant ameliorative effect which appeared independently of any antide-pressant effect [5]. To investigate further the effect of monoamine oxidase (MAO) blockade, we now report data from an open-label trial of selegiline where patients were told they would receive either active agent or placebo at some time during the trial.…”
Section: Oooooooooooooooooooooomentioning
confidence: 99%
“…Quoiqu'il en soit, le manque de consensus entre les différentes études tout comme la diversité des étiologies avancées incitent à penser que le SFC n'est pas une entité pathologique distincte mais un syndrome multifactoriel qui doit être abordé sur les plans somatique, psychologique, et même social. En ce qui concerne les traitements, il semble que certains antidépresseurs (fluoxétine, phenelzine [inhibiteur de la monoamine oxydase]) puissent avoir une action bénéfique lorsque des symptômes tels que dépression, insomnie ou myalgies sont présents [18,19]. Le recouvrement qui existe entre le SFC et la dépression ne permet toutefois pas d'apprécier l'action précise des antidépresseurs.…”
Section: Le Syndrome De Fatigue Chroniqueunclassified